Repositionable Versus Balloon‐Expandable Devices for Transcatheter Aortic Valve Implantation in Patients With Aortic Stenosis. Issue 11 (November 2016) - Pilgrim, Thomas; Stortecky, Stefan; Nietlispach, Fabian; Heg, Dik; Tueller, David; Toggweiler, Stefan; Ferrari, Enrico; Noble, Stéphane; Maisano, Francesco; Jeger, Raban; Roffi, Marco; Grünenfelder, Jürg; et al.
Abstract : Background: The safety and effectiveness of the fully repositionable LOTUS valve system as compared with the balloon‐expandable Edwards SAPIEN 3 prosthesis for the treatment of aortic stenosis has not been evaluated to date. Methods and Results: All patients undergoing transcatheter aortic valve implantation with the Edwards SAPIEN 3 or the LOTUS valve system were included into the Swiss Transcatheter Aortic Valve Implantation Registry. An adjusted analysis was performed to compare the early clinical safety outcome according to the Valve Academic Research Consortium‐2 definition. Between February 2014 and September 2015, 140 and 815 patients were treated with the LOTUS and the Edwards SAPIEN 3 valve, respectively. There was no difference in crude and adjusted analyses of the early safety outcome between patients treated with LOTUS (14.3%) and those treated with Edwards SAPIEN 3 (14.6%) (crude hazard ratio, 0.97; 95% CI, 0.61–1.56 [ P =0.915]; adjusted hazard ratio, 1.03; 95% CI, 0.64–1.67 [ P =0.909]). More than mild aortic regurgitation was <2% for both devices. A total of 34.3% of patients treated with LOTUS and 14.1% of patients treated with Edwards SAPIEN 3 required a permanent pacemaker (HR, 2.76; 95% CI, 1.97–3.87 [ P <0.001]). Conclusions: The repositionable LOTUS valve system and the balloon‐expandable Edwards SAPIEN 3 prosthesis appeared comparable in regard to the Valve Academic Research Consortium‐2 early safety outcome, and the rates of more than mild aortic regurgitation were exceedingly low for both devices. The need for new permanent pacemaker implantation was more frequent among patients treated with the LOTUS valve.